Leading multiple teams: Average and relative external leadership influences on team empowerment and effectiveness. - Luciano, Margaret M.; Mathieu, John E.; Ruddy, Thomas M. (Journal of Applied Psychology, 2013)
External leaders continue to be an important source of influence even when teams are empowered, but it is not always clear how they do so. Extending research on structurally empowered teams, we recognize that teams' external leaders are often responsible for multiple teams. We adopt a multilevel approach to model external leader influences at both the team level and the external leader level of analysis. In doing so, we distinguish the influence of general external leader behaviors (i.e., average external leadership) from those that are directed differently toward the teams that they lead (i.e., relative external leadership). Analysis of data collected from 451 individuals, in 101 teams, reporting to 25 external leaders, revealed that both relative and average external leadership related positively to team empowerment. In turn, team empowerment related positively to team performance and member job satisfaction. However, while the indirect effects were all positive, we found that relative external leadership was not directly related to team performance, and average external leadership evidenced a significant negative direct influence. Additionally, relative external leadership exhibited a significant direct positive influence on member job satisfaction as anticipated, whereas average external leadership did not. These findings attest to the value in distinguishing external leaders' behaviors that are exhibited consistently versus differentially across empowered teams. Implications and future directions for the study and management of external leaders overseeing multiple teams are discussed.